Determinants of Child Marriages of girls in West Bengal - Punendu Modak; Rajyasri Roy (2018)
"The present study aimed to investigate the determinants of girls child marriage in West Bengal. The purpose of the study was to analyze various demographic, socioeconomic, cultural and village level characteristics that are important in determining factors of child marriage in west Bengal."
Keywords: Education